Culture and tourism? Limits and potential of sustainable tourist development in Gorée, Senegal and Ilha de Moçambique, Mozambique - Elisa Magnani (Via@)
The article presents the case of Gorée and Ilha de Moçambique, two small African islands declared World Heritage Sites for their past history connected to the slave trade and their colonial architecture. They are now cultural tourism destinations but, despite being endowed with a relevant historical and cultural heritage, and their relevance for the African and global history, they haven’t find yet a successful way of promoting their cultural resources as a means to reduce poverty, leaving the poor living conditions of the resident society threaten the very survival of the heritage resources. The article presents the results of two fieldwork missions on the islands conducted by the Author, aimed at showing the weaknesses and strengths of the actual tourist management.